Study of Customer Attitude towards Online Banking Services - Pant, Laxmi; Pant, Divya; Ravva, Abhishek; Pant, Santosh; Ojha, Puspa (Nepalese Journal of Management Science and Research, 2025)
This research analyzes the opinion of Nepalese customers about online banking, focusing on the impact of demographic factors (age, gender, education, and income) and six service quality elements (cost, ease of use, awareness, trust and security, accessibility, and speed). A survey was conducted with a sample of 170 respondents from Kathmandu Valley. The correlation, independent t-test, Anova, and other statistical methods showed that attitude toward online banking is influenced by age and income, while gender and education do not have any significant effect. Despite the readiness to accept online banking, the major obstacles to its usage are security concerns and low levels of awareness. These results emphasize the need for banks to develop robust cybersecurity strategies, marketing and educational campaigns that improve customer awareness, and more demographic-based services to meet online banking expectations. Meeting these requirements will enable banks and policy makers in Nepal to facilitate further digital finance inclusion, meet customer expectations, and strengthen the credibility and usefulness of internet banking in the country.